Analisis Faktor-Faktor Yang Berhubungan Dengan Pelaksanaan Senam Hamil Di Wilayah Puskesmas Purwokerto Barat Tahun 2013 - Annisa Dwi Yuniastari; Siti Fatimah P.; Dina Rahayuning P. (Jurnal Kesehatan Masyarakat (Undip), 2014)
Analysis of factors related to the implementation of pregnant gymnastics in purwokerto western region health center: During pregnancy, pregnant women would usually have complaints. Moderated exercise such as pregnancy exercise would make your feet and heels more comfortable. Percentage of antenatal care in health centers of West Navan especially for K1 and K4 already met the target of 95% . The purpose of this studied is analysis of factors associated with the implementation of the health center pregnancy exercise in Navan western region in 2013 . This researched used analytic studied with cross -sectional correlation . The population in this study were all pregnant women in the region checkups Navan West Health Center in 2012 as many as 871 pregnant women then took sample of 59 samples using accidental sampling methode . Analyzed used univariate and bivariate analysis with the chi square test . These results it could be concluded that most of the samples have a relatively good knowledge (67.8 %) ,good attitude (69.5 %) , not working (55.9 %) , support pregnant women during pregnancy (67.8 %) and doing pregnancy exercise (71.2 %). The chi-square statistical test found no relationship between knowledge , attitude and family support with the implementation of the pregnancy exercise with each value p = 0.005 , p = 0.001 and p = 0.005 then found that there was no relationship between job execution pregnancy exercise with p = 0.362